Q. 193.7( 4 Votes )

# If (x + 1) is a factor of 2x^{2}+ kx, then k =?

A. -3

B. -2

C. 2

D. 4

Answer :

Let p (x) = 2x^{2} + kx

It is given that, (x + 1) is a factor of (2x^{2} + kx)

Thus, x = -1 is a factor of (2x^{2} + kx)

∴ p (-1) = 0

2 (-1)^{2} + k (-1) = 0

2 – k = 0

k = 2

Thus, the value of k = 2

Hence, option C is correct

Rate this question :

The zeroes of the polynomial p (x) = x^{2} + x - 6 are

Zero of the polynomial p(x) = 2x + 3 is

RS Aggarwal & V Aggarwal - MathematicsIf find

(i) f (0)

(ii) f (4)

(iii) f (-5)

RS Aggarwal & V Aggarwal - MathematicsIf 2 and -1/3 are the zeros of the polynomial 3x^{3} - 2x^{2} - 7x - 2 find the third zero of the polynomial.

If (x + 1) is a factor of 2x^{2}+ kx, then k =?

If (x^{2}+ kx – 3) = (x – 3 ) (x + 1) then k =?

The zeroes of the polynomial p (x) = x^{2} – 3x are

The zeroes of the polynomial p (x) = 3x^{2} – 1 are

If p(x) = x^{3} + x^{2} + ax + 115 is exactly divisible by (x + 5) then a = ?